Correction: Should All Women with Polycystic Ovary Syndrome Be Screened for Metabolic Parameters?: A Hospital-Based Observational Study. - Hui Li (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0167036.].